Vampire knight. Vol. 17 - Hino, Matsuri (Shojo beat manga., 2012)
"Kaname has returned to Cross Academy to kill Sara Shirabuki. Zero has joined forces with Sara, leaving Yuki in the middle of the conflict. Even if Kaname's ultimate goal is to kill all purebloods, is Yuki ready to fight him?" -- from publisher's web site.